Addendum: Experimental evidence of intrabeam scattering in a free-electron laser driver (2020 New J. Phys.22 083053). (1st March 2022) - Di Mitri, S; Perosa, G; Brynes, A; Setija, I; Spampinati, S; Williams, P H; Wolski, A; Allaria, E; Brussaard, S; Giannessi, L; Penco, G; Rebernik, P R; et al.
Abstract: A conceptual inaccuracy in the calculation of energy spread induced by intrabeam scattering in the presence of linear acceleration is put in evidence. A new self-consistent equation is presented. Two new solutions are provided in the approximation of Coulomb logarithm independent of the particle energy, and for a weak energy dependence. A comparison of the three solutions is shown; it does not imply any noticeable modification to the previously published data, hence the published conclusions remain valid.